2023
DOI: 10.3389/fphys.2023.1106387
|View full text |Cite
|
Sign up to set email alerts
|

Effects of prolonged local vibration superimposed to muscle contraction on motoneuronal and cortical excitability

Abstract: Introduction: Acute effects of prolonged local vibration (LV) at the central nervous system level have been well investigated demonstrating an altered motoneuronal excitability with a concomitant increase in cortical excitability. While applying LV during isometric voluntary contraction is thought to optimize the effects of LV, this has never been addressed considering the acute changes in central nervous system excitability.Materials and Methods: In the present study, nineteen healthy participants were engage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 49 publications
(76 reference statements)
0
2
0
Order By: Relevance
“…The effect of LV on central nervous system excitability has been increasingly well established [34,46]. A reduction in motor neuron excitability assessed at rest or during weak contractions by means of thoracic or cervicomedullary stimulation corroborates the loss of force for durations of 30 min [14,29].…”
Section: Discussionmentioning
confidence: 88%
“…The effect of LV on central nervous system excitability has been increasingly well established [34,46]. A reduction in motor neuron excitability assessed at rest or during weak contractions by means of thoracic or cervicomedullary stimulation corroborates the loss of force for durations of 30 min [14,29].…”
Section: Discussionmentioning
confidence: 88%
“…These effects have been attributed to a decrease in motoneuron excitability by corticospinal electrical stimulation studies (Souron et al, 2019). In addition, intense vibratory stimulation has been found to induce both a decrease in spinal excitability and a cortical excitability modulation revealed by comparing cortical versus thoracic or cervico-medullary evoked potentials (Kennouche et al, 2022;Pfenninger et al, 2023). It should be noted that the duration of these spinal and cortical changes has not been evaluated because the above studies were conducted under acute conditions.…”
Section: Section 3: Evidence Of Long-lasting Excitability Changes Ind...mentioning
confidence: 99%
“…As with spinal tests, several studies have reported changes in cortical excitability after muscle vibration (Souron et al, 2017a). Acute effects, after a single session of FV, are equivocal regarding cortical excitability, showing evidence of potentiation, decrease, or absence of effects in magnetic evoked potentials (MEPs), short intracortical inhibition (SICI), intracortical facilitation (ICF) (Rosenkranz and Rothwell, 2006;Souron et al, 2017a;Kennouche et al, 2022;Pfenninger et al, 2023). The reason for these discrepancies may be due to differences in the frequency, amplitude, duration, and application modes of vibration (Rosenkranz and Rothwell, 2006).…”
Section: Section 3: Evidence Of Long-lasting Excitability Changes Ind...mentioning
confidence: 99%